Embodied, Exploratory Listening in the Concert Hall - Remy Haswell-Martin; Finn Upham; Simon Høffding; Nanette Nielsen (Behavioral Sciences)
Live music can afford novel, transformative aesthetic interactions for individual audience members. Nevertheless, concert research tends to focus on shared experience. In this paper we offer an account of exploratory listening that foregrounds embodied–enactive engagement and affective resonance through close analysis of the music, physiological measurements, and reflections from interviews. Our analysis centres on data collected from two musician audience members about one specific piece out of a larger interdisciplinary project involving concerts given by the Stavanger Symphony Orchestra and The Norwegian Radio Orchestra in March and June of 2024. Through the combination of in-depth phenomenological interviews with musically skilled audience members and measurements of breathing and body motion, we explore aesthetic enactment beyond common patterns of ‘synchronised’ response, focusing on audience members’ experiences of Harald Sæverud’s ‘Kjempeviseslåtten’ (The Ballad of Revolt) (1943). We find forms of absorbed, both imaginative and embodied involvement, of listeners enacting meaningful contact with, and pathways through, the music that in some ways corroborate crowd patterns but also reveal exploratory expertise and idiosyncratic affective orientations.